p53 inhibits CTR1-mediated cisplatin absorption by suppressing SP1 nuclear translocation in osteosarcoma - Yong, Lei; Shi, Yan; Wu, Hai-Long; Dong, Qi-Yuan; Guo, Jing; Hu, Li-Sheng; Wang, Wen-Hao; Guan, Zhi-Ping; Yu, Bin-Sheng (Frontiers in Oncology, 2023)
Background Osteosarcoma (OS) is a malignant bone tumor mainly affecting children and young adolescents. Cisplatin is a first-line chemotherapy drug for OS, however, drug resistance severely limits the survival of OS. Nevertheless, cellular factors in cisplatin resistance for OS remain obscure. In this study, the function and potential mechanism of p53 in cisplatin absorption were explored in OS cells. Methods The CRISPR-Cas9 gene editing technology was performed to obtain p53 gene knock-out U2OS cells. The p53 over-expression 143B cell line was established by lentivirus-mediated virus infection. Moreover, the functions of p53 and CTR1 in cisplatin absorption were assessed by inductively coupled plasma mass spectrometry (ICP-MS) through CTR1 over-expression and knock-down. Further, the DNA binding activity of SP1 on CTR1 gene promoter was determined by dual-luciferase assay and chromatin immunoprecipitation (ChIP) assay. The functional regulation of p53 on SP1 was studied by nucleocytoplasmic separation assay and electrophoretic mobility shift assay (EMSA). The interaction between p53 and SP1 was verified by Co-Immunoprecipitation assay. Results Under cisplatin treatment, p53 knock-out promoted CTR1 expression and cisplatin uptake, while p53 overexpression inhibited CTR1 expression and cisplatin uptake. Moreover, p53 regulated CTR1 level not by binding to CTR1 promoter directly but by suppressing the nuclear translocation of transcription factor specificity protein 1 (SP1). It was verified that SP1 is directly bound with CTR1 promoter. SP1 overexpression stimulated CTR1 expression, and SP1 knock-down attenuated CTR1 expression. Conclusion The p53 might function as a negative regulator in CTR1 mediated cisplatin absorption, and the p53-SP1-CTR1 axis is a target for cisplatin resistance.